Estilos de aprendizaje en los alumnos del cuarto grado de educación secundaria de una institución educativa de Ventanilla - Chiara Bellido, Elízabeth Liliana (2011)
The purpose of the next investigation is to know the styles of learning that the students have in the fourth grade of high school in an educational institution of Ventanilla and then establish association between the sex of the sample and the dimensions of the variable of study. For that, we worked with a sample of 109 students, boys and girls that are the total of the fourth grade students registered in the year 2009, 50 are female and 59 are male, the sample is not probabilistic. The applied instrument is the questionnaire of Honey- Alonso that determines the preference according the style of learning of the students. So, it concluded that exists predominance in high level in the four styles of learning in both sex. So, the most considerate the pragmatic style.